Ashenden : or the British agent - Maugham, W. Somerset (heinemann , Mandarin, 1967)
Inspired by Maughams's own experiences as a British secret agent in World War I, this series of stories features a fictional spy, John Ashenden, whose dangerous assignments entangle him with traitors, assassins and beautiful but treacherous women.